P739 Novel rapid test for improved diagnosis of active syphilis at the point of care. (14th July 2019) - Pham, Minh; Garcia, Mary; Van, Huy; Technau, Karl; Wise, Amy; Anderson, David
Abstract : Background: Syphilis has been and still is one of the greatest global health concerns. Syphilis can seriously damage the nervous system of infected individuals including infants born to infected mother. Treatment of syphilis is simple and effective with penicillin but diagnosis is challenging, particularly in resource-constrained settings, due to the need for a laboratory-based confirmatory test. Current point of care (POC) tests for syphilis are available but cannot distinguish active infections from past treated infections with a misclassification rate of up to 50% (low specificity). We developed a prototype rapid POC test (IgA Confirm) that can differentiate active syphilis from past treated infections at the point of care. Methods: We conducted a prospective diagnostic accuracy study to assess the specificity (and sensitivity) of the IgA Confirm test in identifying active syphilis infections classified by Treponema pallidum Antibobody (TPAb) and rapid plasma regain (RPR) laboratory serology. Between June-December 2018, 500 pregnant women attending Rahima Moosa Mother and Child hospital, South Africa were recruited and provided venous blood samples for syphilis testing including the IgA Confirm (index) and laboratory serology (reference) tests. Results: The IgA Confirm demonstrate a sensitivity of 100% (5/5) for identifying samples with active syphilis infections (TPAb positive and RPR positive); 100% (9/9) specificity for identifying samples with past or treated infections (TPAb positive, RPR negative) and, 99.4% (484/487) specificity for samples with no evidence of syphilis (TPAb and RPR negative). Conclusion: This study showed that the IgA Confirm test has the ability to identify active syphilis infection and meet the WHO Target Product Profile for syphilis confirmatory testing. Future study is needed to further evaluate diagnostic performance of the test in high prevalence setting. Disclosure: No significant relationships.